The veterinarian as trainer of health community and endemic agents on the prevention of accidents caused by venomous animals (Research, Society and Development, 2020)
The Veterinary Medicine stands out in public health, for acting in health promotion, identification of risk factors and establishment of measures of prevention and control of diseases and injuries. In order to carry out a survey on the prior knowledge of Agents Health Community and Endemic Disease Control Agents (AHC / EDCA) regarding the relationship between public health and veterinary medicine, and issues related to the main species of venomous animals involved in acidentes. The study comprehended three steps.  the first step of the research was the creation and application of questionnaires. The second step represented a training course on the prevention of accidents caused by venomous animals for AHC and EDCA. Finally, the third step involved the questionnaires reapplication at the end of each course meeting with a related subject. Out of 46 participants, 58.70% (27) were AHC and 41.30% (19) EDCA. In the questionnaires, participants were asked before the course beginning if they knew how to prevent accidents by venomous animals. The results showed that 84.78% (39) knew how to prevent accidents, and after the course, all participants responded correctly. Also, in the questionnaires, participants were asked for the definition of venomous animal. Before the course, 43.48% (20) were able to define it, and after the course 71.74% (33). The study showed the importance of education in health practices and the role of veterinarians in training AHC and EDCA, contributing then for the multiplication of health knowledge in society.